Interlocking directorates in Hong Kong’s financial sector. - Liang, Peishan. (2012)
Interlocking directorates refers to situations where members of corporate board of directors serve on the boards of multiple corporations. In a public-listed company, the board of directors functions as the guardian to good corporate governance, and is expected to hold the management accountable to shareholders and regulators. A director who sits on multiple boards may not be able to exercise his judgment independently and may not have sufficient time and energy to commit to his duties. This raises questions about the quality and independence of board decisions. Hong Kong, being an international cosmopolitan financial center, has been developing and refining its corporate governance frameworks. It is the aim of this dissertation to look into the extent and structure of interlocking directorates among public-listed companies from the Hong Kong financial sector.